The opioid crisis - Harris, Duchess; Katz, Nina Judith (Special reports (Essential Library (Firm)), 2019)
Examines the current opioid crisis, discussing the history, contributing factors, and complications arising from the easy access to narcotics. Discusses recent science on addiction, and details what's being done to combat the problem. Includes sidebars, a glossary, resources for further information, maps, and color photographs.